2016
DOI: 10.1055/s-0042-105177
|View full text |Cite
|
Sign up to set email alerts
|

Erfassung von Patientenübergriffen 2008–2015 in zwei psychiatrischen Kliniken: Ergebnisse und Implikationen

Abstract: Studies on the frequency and the overall trend in recent years of aggressive assaults by patients in German psychiatric hospitals are scarce. We investigated the frequency of physical aggression by patients between 2008 and 2015 in two hospitals for psychiatry and psychotherapy. Aggressive and violent events were routinely assessed (spontaneous reports) and were analyzed in a differentiated way. The frequency of aggressive behavior of patients towards others showed a slightly, but significantly increase since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
5
1
1
Order By: Relevance
“…Our results present a rate for patients that demonstrated violent behavior in a prison hospital that ranged from 3.2 to 15.9%. This rate is in the range of rates reported from psychiatric inpatients in community hospital care (2–4). Regarding trends, there was no statistically significant increase in violent behavior in the last 20 years regarding the psychiatric ward of the Berlin prison hospital.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Our results present a rate for patients that demonstrated violent behavior in a prison hospital that ranged from 3.2 to 15.9%. This rate is in the range of rates reported from psychiatric inpatients in community hospital care (2–4). Regarding trends, there was no statistically significant increase in violent behavior in the last 20 years regarding the psychiatric ward of the Berlin prison hospital.…”
Section: Resultsmentioning
confidence: 55%
“…Schizophrenia proved to be a statistically significant marker for the patients in the violent group what is in accordance to the international literature on psychosis, substance abuse, and violent behavior (8, 11, 30). Interestingly, rates of violent behavior did not exceed the reported rates from general psychiatry (2–4). Wolf et al .…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Zudem wird eine psychiatrieerfahrene Person eingeladen, die ihr Stigmaerleben beschreibt und mit den anderen KursteilnehmerInnen in Erfahrungsaustausch tritt. Gemeinsam werden Lösungsund Handlungsmöglichkeiten zur Stigmabewältigung erarbeitet, reichend vom Umgang mit entwertenden sprachlichen Formulierungen bis hin zur Verarbeitung von äußerst übergriffig erlebten Situationen, wie beispielsweise mechanische Fixierungen [26,27].…”
Section: Abstract Objectiveunclassified
“…The rate of 7.7% reported from a hospital in Northrhine Westfalia some years later by Ketelsen et al [16] was still higher. More recently, Mueller et al [21] reported a significant increase of violent incidents between 2008 and 2015 in a hospital in the State of Hesse, but on a rather low level (from 1.78% up to 3.32% of all admissions). In a subsequent article considering the following year, 2016, a pattern of increase could not be confirmed [22].…”
Section: Introductionmentioning
confidence: 99%